Caracterização do perfil imunológico de indivíduos com sepse - Rodrigo Junio Rodrigues Barros (2013)
The severity of sepsis is associated with the inability of the immune system to control the growth of the microorganism during infection. Several mechanisms have been proposed to explain how microorganisms cause immune infections. Some explanations are based on the activity of lymphocytes and monocytes with concomitant production of pro-inflammatory and anti-inflammatory molecules. However, the involvement of T cells CD4 and CD8 and monocytes in sepsis is still unknown. The characterization of these cells and their role has been the subject of intense study due to its critical role in maintaining and/or control of the response to microorganisms causing sepsis In this study we evaluated the phenotypic profile of CD14+ monocytes and CD4+ and CD8+ T lymphocytes from patients with sepsis. Additionally, we analyzed the expression of activation (CD69), costimulatory molecules (CD80 and CD86), apoptotic markers (granzyme A and B) and TOLL LIKE receptors (TLR2 and TLR4), as well as proinflammatory cytokines (IL-1, IL-17, TNF- and IFN-g) and anti-inflammatory cytokine (IL-10). Our results showed that CD14+ monocytes from septic patients present lower expression of TLR-2, CD86, HLA-DR and increased expression of TNF-. These patients also present higher frequency of CD4+CD62L- CD69+ activated T cells in peripheral blood when compared to healthy donnors. The CD4+T cells from septic patitens present higher levels of IFN-, IL-17 and IL-10 and CD8+ T cells increased frequency of granzyme A and IFN- when compared to healthy subjects. In conclusion, our results provide a better understanding of the phenotypic profile of monocytes and T cells from patients with sepsis and demonstrated the plasticity of these cells and may act in suppression, modulation and even in the maintenance of inflammation triggered by sepsis.